Pengaruh intensitas modal, intensitas persediaan, pertumbuhan penjualan dan profitabilitas terhadap agresivitas pajak - Christina, Metta Wira; Wahyudi, Ickhsanto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Along with the development of the global economy, demanding tough competition in business, all companies are competing to do everything they can to face the competition. Companies that are not able to compete will slowly begin to be eliminated from the business world because they are unable to maintain their company's performance. As a profit-oriented company, of course the company will try to maximize profits in various ways. One of the company's strategies to streamline profits is to carry out tax aggressiveness, namely a strategy to reduce the tax burden so that the company obtain more optimal profits. This study aims to obtain empirical evidence about the effect of capital intensity, inventory intensity, sales growth, and profitability on tax aggressiveness The methodology that the researcher uses is quantitative data, namely the financial statements of health sector companies listed on the Indonesia Stock Exchange (IDX) to test the hypothesis about the strength of the determinant variable (Independent Variable on tax aggressiveness in this study, regression analysis was used . The results of the stud conclude that capital intensity has no effect on tax aggressiveness, while inventor intensity, sales growth, and profitability have a negative effect on tax aggressiveness